Early Postoperative Serum Carcinoembryonic Antigen Is a Stronger Independent Prognostic Factor for Stage II Colorectal Cancer Patients Than T4 Stage and Preoperative CEA - Fenqi, Du; Yupeng, Liu; Qiuju, Zhang; Chao, Yuan; Wenjie, Song; Tianyi, Xia; Junnan, Guo; Weinan, Xue; Xiufeng, Jiang; Junge, Bai; Chenyang, Jia; Hua, Xi; et al. (Frontiers in Oncology, 2022)
Background: Due to the heterogeneity in the prognosis of stage II colorectal cancer (CRC), more accurate predictors are needed to help with assessing the prognosis. Methods: Patients with stage II CRC from January 2007 to December 2015 were included. Receiver operating characteristic (ROC) curves was used to obtain the cutoff value of early postoperative CEA, and the area under curves (AUCs) were used to estimate predictive abilities of early postoperative CEA, preoperative CEA and T stage for prognosis. The stepwise regression method was used to screen the factors included in the Cox regression analysis. Before and after propensity score (PS) -adjusted Cox regression and sensitivity analysis were used to identify the relationship between early postoperative CEA and prognosis. Kaplan-Meier survival curves were used to estimate the effects of early postoperative CEA on prognosis and guiding value for adjuvant chemotherapy. Results: We included 1081 eligible patients. ROC curves suggested the cutoff value of early postoperative CEA was 3.66 ng/ml (P ＜0.001) and AUC showed early postoperative CEA was the most significant prognostic marker in stage II CRC (P = 0.0189). The Cox regression and sensitivity analysis before and after adjusting for PS both revealed elevated early postoperative CEA was the strongest independent prognostic factor of OS, DFS, and CSS (P ＜0.001). Survival analysis revealed that patients with elevated early postoperative CEA had lower OS (53.62% VS 84.16%), DFS (50.03% VS 86.75%), and CSS (61.77% VS 90.30%) than patients with normal early postoperative CEA (P < 0.001). When the postoperative CEA was positive, the preoperative CEA level showed no significant effect on the patient’s prognosis (P > 0.05). Patients with a CEA ratio ≤0.55 or CEA absolute value ≤-0.98 had a worse prognosis (all P-values were < 0.001). Survival analysis suggested that adjuvant chemotherapy for stage II CRC patients with elevated early postoperative CEA may improve the CSS (P = 0.040). Conclusions: Early postoperative CEA was a better biomarker for prognosis of stage II CRC patients than T stage and preoperative CEA, and has the potential to become a high-risk factor to guide the prognosis and treatment of stage II CRC patients.